LEAF AREA INDEX DERIVED FROM HEMISPHERICAL PHOTOGRAPH AND ITS CORRELATION WITH ABOVEGROUND FOREST BIOMASS - Basuki, Tyas Mutiara (Indonesian Journal of Forestry Research, 2015)
Leaf area index (LAI) is one of key physical factors in the energy exchange between terrestrial ecosystem and atmosphere. It determines photosynthesis process to produce biomass and plays an important role in performing forest stand reflectance, therefore building relationships between LAI and biomass from field measurement can be used to develop allometric equations for biomass estimation. The purposes of this research are: 1). To develop relationships between diameter at breast height (DBH) and crown biomass (leaves; leaves + twigs + branches; Â 2).To develop relationships between leaf area index (LAI) and crown biomass; LAI and Total Above-ground Biomass (TAGB). A destructive sampling was conducted to build allometric equations. The DBH measurements from 52 sample plots were used to build relationships between DBH and crown biomass, as well as LAI and crown biomass and also TAGB. A hemispherical photograph was used to record LAI. The research was carried out in East Kalimantan. The results showed that strong coefficient of determinations (r2) were found between natural logarithmic (ln) DBH and crown biomass ranging from 0.77 to 0.93. The correlations (r) between LAI and leaves; leaves+twigs+branches; TAGB were arround 0.75 and the r2 were 0.564; 0.570; and 0.572, respectivelly. Â Although LAI measuremnt using hemispherical is considered tedious, however the results are useful for validation of LAI measueremnts using remote sensing techniques. Improvement of r2 between LAI and biomass can be conducted by proper time of LAI measurement, immediately after sunrise or sunset.